Human-mediated dispersal in insects - Gippet, Jérôme Mw; Liebhold, Andrew M; Fenn-Moltu, Gyda; Bertelsmeier, Cleo (Current opinion in insect science, 2019)
Central to the problem of biological invasions, human activities introduce species beyond their native ranges and participate in their subsequent spread. Understanding human-mediated dispersal is therefore crucial for both predicting and preventing invasions. Here, we show that decomposing human-mediated dispersal into three temporal phases: departure, transport and arrival, allows to understand how the characteristics of human activities and the biological traits of species influence each phase of the dispersal process, and ultimately govern invasion pathways in insects. Integrating these precise mechanisms into future invasion models should increase their realism and generalization for any potential insect invader. Moreover, understanding these mechanisms can provide insight into why some invasive insects are more widely distributed than others, and to estimate risks posed by species that have not yet been introduced.
Keywords: lidské činnosti; Insecta; zavlečené druhy; Animal Distribution; Introduced Species; hmyz; Animals; lidé; rozšíření zvířat; Humans; zvířata; Human Activities